Theological and philosophical responses to syncretism : beyond the mirage of pure religion - Fridlund, Patrik.; Vähäkangas, Mika. (Philosophy of Religion - World Religions, 2017)
Theological and Philosophical Responses to Syncretism: Beyond the Mirage of Pure Religion by Patrik Fridlund and Mika Vähäkangas (editions.) starts from the observation that there is a substantial gap between religions' self-understanding and the empirical results of religious studies concerning religious blending. Even in theology of religion, one often portrays religions as if they were entities fundamentally separate from each other. The aims of this book are to elaborate theologically the consequences of syncretism to Christian faith and of syncretism to philosophy. By creating a critical interchange between theological, philosophical and empirical approaches to religion, this book challenges the conventional views of purity of religions prevailing in theology and philosophy as well as proposes theological and philosophical ways forward. Contributors are: Jonas Adelin, Stephen Bevans, Gavin d'Costa, Patrik Fridlund, Lotta Gammelin, Elizabeth Harris, Jerker Karlsson, Paul Linjamaa, Kang-San Tan, Mika Vähäkangas.